Adoption of the open innovation paradigm within the Sports Industry - Sexton, Larissa-Elaine (2017)
Innovations play a pivotal role in today’s corporate strategy. The ability to innovate is a basic requirement to persist in the global competition and to stay successful in the long run. The sports industry is characterised by an intense, dynamic and competitive environment. The customer’s lifestyle orientation becomes increasingly important and product lifecycles get shorter and more individualistic. With those changing conditions and evolving demand, companies have to pay close attention to their innovation process. To respond to these challenges, more and more companies open up their innovation process and look for partners with complementary expertise to collaborate with. This is called open innovation. The thesis aims to answer the research question, namely: “How companies in the sports industry use open innovation and which methods are implemented during the innovation process?” In order to answer this question, a multiple-case study analysis was conducted. Three principal companies – Canyon GmbH, Mizuno Corporation and Under Armour – as well as one crowdsourcing platform – ISPO Open Innovation – have been investigated. The main findings show that all companies are highly dependent on innovations and have approached different ways to interpret and put open innovation into practice. Overall, the companies follow to some extent a unidirectional approach, meaning they rather enrich internal projects with inflows of external knowledge than find new paths to markets by providing their know-how and technologies to the external environment. Two companies are even more protective and closed regarding their own resources. They concentrate on collaborations with trusted partners, which offer a higher degree of control, security and familiarity. Especially larger and well-established companies fear unbeneficial leakage of knowledge and technologies to externals through open innovation. To conclude, the degree of openness and the way sports companies collaborate is rather organic and restricted to some extent. However, the development of open innovation strategies indicates that openness is imperative in order to stay competitive in the long run.